Elisabeth Elliot: joyful surrender - Benge, Janet (Christian heroes: then & now, 2010)
"The life of missionary Elisabeth Elliot, who began working among the Auca Indians in South America after her husband's death. Returning to the United States after many years as a missionary, Elliot became widely known as a Christian author and speaker"--Provided by publisher